The Routledge handbook of far-right extremism in Europe - Kondor, Katherine HerausgeberIn; Littler, Mark HerausgeberIn (Routledge international handbooks, 2024)
"This book deals with the rise of right wing in Europe and the development of right wing movements in Europe across all countries of the continent"--